Estresse em arroz (Oryza sativa L.): Correlação dos efeito de dois ambientes de cultivo. - Danielowski, Rodrigo (2013)
Rice (Oryza sativa. L) is the second most produced cereal worldwide. Soil salinity is one of the most severe abiotic stresses for various crop species. Currently, 6% of arable land on the planet have a limitation due to salinity levels in the soil, it is estimated that by the year 2050, 50% of agricultural soils present limitations due to soil salinity. Rice is one of the crops most sensitive to soil salinity, reductions in productivity are observed at levels of electrical conductivity of 3.0 dS m-1. The hydroponic growing systems are being increasingly used in scientific studies, and a major advantage of this technique is the control of the studied factors and homogeneity of the environment. This study aimed to evaluate genotypes of rice germplasm bank of EMBRAPA temperate in two hydroponic growing systems effecting the correlation of the results obtained in the two systems. The one experiment was conducted in a greenhouse and the second in a room with controlled temperature and photoperiod. The nutrient solution used in the experiments was YOSHIDA et al. (1976) with some adaptations, and salinity levels used were 0, 30, 60 and 90 mM NaCl. The correlation study was conducted with 24 genotypes evaluated in two experiments, adopting also only 0, 30 and 60 mM as dose factors. The two cultivation environments provided genotype variation of the response as a function of NaCl concentration levels. The cropping system in a controlled environment at the level of 90 mM caused the death of almost all plants. The correlation study revealed no association between the two culture environments, should be made a further study in field conditions to validate and compare the efficiency of the methods.